Mineral Composition of Some Turkish Durum Wheat Genotypes - OKTEM, ABDULLAH; GULGUN OKTEM, AYSE (Asian Journal of Chemistry, 2010)
This study was conducted to determine mineral composition of some durum wheat genotypes. The research was carried out during 2001 and 2002 growing seasons in Sanliurfa, Turkey. Thirty one durum wheat genotypes were grown in the field and kernel samples analyzed by an atomic absorption spectrometry. Some minerals such as calcium, magnesium, iron, zinc, copper, manganese, molybdenum and boron were determined in kernel of wheat genotypes. Genotypes were statistically significant (p < 0.01) for all minerals in both years. In the wheat kernel, calcium ranged from 0.13 to 0.33 %, magnesium 0.16 to 0.28 %, iron 29.3 to 45.6 mg kg-1, zinc 16.5 to 32.6 mg kg-1, copper 4.03 to 9.79 mg kg-1, manganese 37.3 to 47.5 mg kg-1, molybdenum 3.34 to 5.71 mg kg-1 and boron 8.8 to 15.2 mg kg-1. Some durum wheat genotypes such as Dicle-74, C.1252, Kiziltan-91, Kunduru-1149, Altar-84, Zenith and Gedifla had the richest mineral contents among other genotypes.